Percutaneous catheterisation of the radial artery in newborn babies using transillumination. - Pearse, R G (1978)
A technique for inserting radial artery catheters percutaneously in newborn babies using transillumination is described. Catheterisation was successful in 69% of the 107 babies in whom it was attempted. In the last 30 attempts there was an 85% success rate with an average useful life of 100 hours. The average weight of these babies was 1405 g, with a range of 620--4250 g. The method has several advantages over previous methods.